Ultrasound-Assisted Extraction of Micro- and Macroelements in Fruit Peel Powder Mineral Supplement for Osteoporosis Patients and Their Determination by Flame Atomic Absorption Spectrometry - Muhammad Saleem; Arjumand Iqbal Durani; Rima D. Alharthy; Mahmood Ahmed; Muhammad Imtiaz Shafiq; Abdul Hameed; Syed Mubasher Hussain; Waqas Bashir (Journal of Chemistry)
Osteoporosis is a worldwide disease depicted by the reduced bone mass, an adequate supply of minerals is needed to support bone remodeling, and their deficiency causes bone-related diseases, osteoporosis in particular, and has osteoprotective effects. The aim of this recent research was to quantify the micro- (Mn, Fe, Cu, and Zn) and macroelements (Mg, K, and Ca) in the peel powder of some common fruits (pomegranate, orange, lemon, mango, and grapefruit) by flame atomic absorption spectrometer (FAAS). The extraction of micro- and macroelements in peel powder was done by using dilute acids in an ultrasonic bath. Apple leaves were used as standard reference material (SRM, NIST 1515) to optimize the ultrasound-assisted extraction (UAE) method at varied operating parameters. Maximum response was obtained for extracting of minerals in 500 mg SRM at 60°C temperature, setting a vortexing time of 5 min while using 5.0 mL extracting agent HNO3 (0.5 M)-H2O2 (10%) at 90% sonication amplitude of ultrasound bath for 6 min. While analyzing the SRM, the percentage recovery was obtained in a range between 96.8 and 102.7% to assure the accuracy whereas repeatability (n = 10) study in terms of % RSD yielding ≤2.29 supports well the precision of the proposed method, and limits of quantitation (μg/g) were 0.034, 0.061, 0.065, 0.057, 0.017, 0.175, and 0.053 for Mn, Fe, Cu, Zn, Mg, K, and Ca, respectively. The proposed UAE method was reliable, efficient, and advantageous over the conventionally employed acid digestion method with regard to less consumption of reagents and short analysis time for the determination of micro- and macroelements in fruit peel powder.